Divergent patterns of leucocyte locomotion in experimental post-traumatic osteomyelitis. - Müller, C. (1984)
Leucocyte locomotion (LL) was evaluated in guinea-pigs with experimental post-traumatic osteomyelitis. Surgical procedure (fracture of the right femur), the number of micro-organisms applied to the fractured site and the time sequence of investigations were kept constant. After the right femur of guinea-pigs had been fractured, the animals were divided into three groups: in group I the fractured site remained uninfected, while in groups 2 and 3 the fractured sites were infected with either Escherichia coli (10(5] or with Staphylococcus aureus (10(4]. In a fourth group, guinea-pigs were anaesthesized only, without any further trauma. LL was significantly depressed in all three groups following trauma on postoperative day 5 as compared to pre-operative levels (P less than 0.01), but had remained normal in guinea-pigs which had been anaesthesized only. While LL returned to pre-operative levels and stayed normal in uninfected guinea-pigs and those which had been infected with E. coli, LL levels fell significantly (P less than 0.05) in guinea-pigs which had been infected with Staph. aureus on postoperative day 55 and remained depressed throughout the observation period of 90 days. These findings emphasize that defects in LL are connected with the infectious agent and are not merely secondary to the process in the osseous tissue.